Mixed Impact of Climate Change on Cold Season Residential Electricity: A Case Study of Lanzhou and Lhasa - Xia, Cuihui; Yao, Tandong; Hou, Haowen; Wang, Pengling (Frontiers in Earth Science, 2022)
Extreme weather induced by climate change has triggered large-scale power outages worldwide, particularly during the cold season. More insight into the climatic impacts (especially those of precipitation) on cold season residential electricity consumption (REC) is needed. This study quantified the climatic impacts on REC, with a focus on precipitation, and projected the associated changes under representative concentration pathways (RCPs) 2.6, 4.5, and 8.5 climate change scenarios in Lanzhou and Lhasa, two cities in China with distinctive cold season climates. The climatic impacts on REC in both cities are driven by heating-related demand. A stronger precipitation impact during the cold season was observed in both cities, since precipitation (particularly snowfall) boosts electricity consumption during the cold season. As the two cities become warmer and wetter, increased precipitation will offset the impact of warming on REC, with Lanzhou being more strongly affected. Based on the projections for Lanzhou, the offsetting effect will be more pronounced during the cold season across all scenarios, and will be particularly strong under RCP 2.6. For the remainder of the year, the effects of increased precipitation and warming will have competing importances under the RCP 4.5 scenario, whereas temperature effects will generally dominate the climatic impacts under the RCP 8.5 scenario. These results provide new insights for future cold season climate–energy studies and can be used to improve regional climate adaptation policies. We also propose a method to project climate-based REC changes which is compatible with potential early-warning projects to protect against extreme weather-induced power outages.